Understanding doctors’ and nurses’ roles in the Islamic medical practice and rukhsah solah in a Shariah-compliant hospital - Mohd Arifin, Siti Roshaidai; Mohd Nazir, Nur Afiqah; Samsudin, Suhaiza; Daud, Normadiah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Introduction: Implementing Islamic medical practice (IMP) within a Shariah-compliant hospital is challenging because of the lack of knowledge and spiritual care among healthcare practitioners (HCPs), especially nurses and doctors. Thus, this study aims to determine the understanding of IMP and the associated factors among HCPs in a Shariah-compliant hospital. Methods: This cross-sectional study was conducted using questionnaires distributed among nurses and doctors working in a Shariah-compliant hospital in Pahang, Malaysia. Results: A total of 152 nurses and doctors participated in this study. Resultantly, 80.3% (n = 122) of the subjects had a high understanding of IMP, and only 50% (n = 76) had a good level of knowledge regarding rukhsah solah. Furthermore, the participants’ IMP understanding level was associated with their years of working experience, position and gender (p < 0.05). In addition, the rukhsah solah was associated with the departments (p < 0.05). Conclusion: The study findings suggested more training on rukhsah solah is essential among HCPs, especially those working in a Shariah-compliant hospital to support the IMP implementation.